2013
DOI: 10.1287/isre.1120.0439
|View full text |Cite
|
Sign up to set email alerts
|

Research Note—Do Large Firms Become Smaller by Using Information Technology?

Abstract: T he relationship between information technology (IT) and a key organizational design variable, firm size, is an important area of study, particularly given the ongoing transition to an information-based economy. To better understand the more nuanced aspects of the relationship, we formulated a bidirectional and time-lagged model that incorporates different perspectives from organizational theories and transaction cost economics. Our two models-the bidirectional and one-year lagged model and the bidirectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 90 publications
(171 reference statements)
1
19
0
Order By: Relevance
“…Subsequent studies have provided empirical support for this theoretical argument by linking greater IT investment to operational and strategic coordination (Sanders 2008), smaller firm size and to information exchange and integration (Dennis 1996). Moreover, Im, Grover, and Teng (2013) went further and showed that this IT-firm size linkage can be explained by the negative relationship between IT investment and coordination cost. Recent explosion of the use of mobile devices, such as smart phones, becomes part of the Bring Your Own Device (BYOD) movement, providing further momentum for better IT-facilitated coordination in organizations (Wirthman 2013).…”
Section: It-facilitated Coordinationmentioning
confidence: 95%
“…Subsequent studies have provided empirical support for this theoretical argument by linking greater IT investment to operational and strategic coordination (Sanders 2008), smaller firm size and to information exchange and integration (Dennis 1996). Moreover, Im, Grover, and Teng (2013) went further and showed that this IT-firm size linkage can be explained by the negative relationship between IT investment and coordination cost. Recent explosion of the use of mobile devices, such as smart phones, becomes part of the Bring Your Own Device (BYOD) movement, providing further momentum for better IT-facilitated coordination in organizations (Wirthman 2013).…”
Section: It-facilitated Coordinationmentioning
confidence: 95%
“…In essence, organizing divisions (internal to the firm) around customer groups (external to the firm) should better position the firm to improve customers' experience and thus increases satisfaction, though at the expense of internal simplicity (Gulati 2007, Homburg et al 2000. Coordinating costs, defined as the expenses incurred from managing interdependent functional activities across internal units, suppliers, and customers (Ray et al 2009, Bendoly et al 2012, Im et al 2013, are higher when external, front-end, customer considerations are prioritized in organizing back-end functional activities.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…A customer-centric structural design prioritizes communication about and knowledge of specific customer groups over clarity in internal and back-end functional operations (Day 2006, Gulati 2007. We argue that a customer-centric structure will increase a firm's coordinating costs, or the expenses incurred from managing interdependent functional activities across internal units, suppliers, and customers (Ray et al 2009, Im et al 2013. First, a customer-centric structure employs more resources in communication and decisionmaking processes, because complex reporting relationships arise between front-end (customer-facing) and back-end (product-producing) operation centers.…”
Section: Linking Customer-centric Structure Tomentioning
confidence: 99%
See 2 more Smart Citations